FUNGSI KOMUNIKASI INTERPERSONAL TERHADAP KESEHATAN MENTAL SISWA DI ERA WABAH COVID-19 - B, Irvan Irviana; Hendriana, Heris; Alawiyah, Tuti (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study is predicated on the hypothesis that victims of psychosocial stress brought on by the pandemic are a particularly vulnerable group that need preventive measures to assist them in overcoming mental health concerns via the power of interpersonal communication. family grouping that includes both parents and their children This study's objective was to investigate how maintaining open lines of communication between parents and their adolescents influenced the mental health of the adolescent participants in the midst of the Covid-19 outbreak. This inquiry has a strong emphasis on many theoretical frameworks, including those pertaining to communication, interpersonal communication, parents, adolescents, and mental health. For the purpose of this inquiry, the qualitative descriptive technique was used. Participants in this study are members of the community who are also parents of adolescents. These parents were selected for participation in the study using a methodical sampling pro kucedure. The majority of the data for this research came through in-depth interviews, which served as the main technique of data gathering. In spite of the prevalence of the COV virus, the researchers discovered that maintaining open lines of communication between parents and adolescents was beneficial to the adolescents' mental health. All of these roles, informing, teaching, monitoring, and motivating a kid, are fundamental components of communication between parents and their children. The role of parents as communicators makes adolescents' mental health more important for their physical, mental, spiritual, and social development.